FORMULASI UJI AKTIVITAS ANTIOKSIDAN DAN UJI KARAKTERITIK FISIK SEDIAAN KRIM EKSTRAK DAUN PEPAYA (Carica Papaya L.) SEBAGAI KRIM PELEMBAB KULIT - Muhammad Lathoiful Minan; Muhammad Nurul Fadel; Muhammad Khudzaifi (Nusantara Hasana Journal, 2025)
Papaya leaves are known to contain high levels of antioxidants such as flavonoids, α- tocopherol, and ascorbic acid, which help combat free radicals that cause premature aging. This study aimed to evaluate the stability and antioxidant activity of a cream formulated with 70% ethanol extract of papaya leaves using the DPPH method. A total of 3000 g of young papaya leaves were macerated with 70% ethanol, yielding 56.38 g of thick extract, which was then formulated into a cream. The cream was evaluated through organoleptic tests, homogeneity, pH, spreadability, emulsion type, viscosity, and antioxidant activity. Results showed the cream was stable in terms of odor and form, with a pH range of 5–7, spreadability between 5.8–6.2 cm, homogeneous emulsion, and viscosity ranging from 5003–5990 cP. The highest antioxidant activity was observed at 3.5% concentration (78.45%), while the negative control was 222.4 and quercetin as a reference showed 9.08%. It was concluded that the cream formulated from 70% ethanol extract of papaya leaves demonstrated good stability and strong antioxidant activity.